Zooplankton and Water Quality in Yakruea and Phromlaeng Streams of Nam Nao National Park, Phetchabun Province - อธิบาย ศุจีภรณ์ (KKU Science Journal, 2014)
Species diversity of rotifers, cladocerans, and cyclopoid copepods in headwater streams of Nam Nao National Park, Phetchabun Province was investigated. Samples were qualitatively collected in May 2012, January and April 2013 using 60 µm mesh size plankton net from three sampling sites in Yakruea Stream and one sampling site in Phromlaeng Stream. In addition, the twelve physico-chemical parameters, including water depth, stream width, velocity, light intensity, water temperature, turbidity, dissolved oxygen, electrical conductivity, total dissolved solid, pH, nitrate content and orthophosphate content were measured. Eleven species of rotifers, 6 species of cladocerans, and 4 species of cyclopoid copepods were identified. Platyias quadricornis (Ehrenberg) was collected from all 4 sampling sites. Eight species including Dipleuchnis propatula (Gosse), Lecane bulla (Gosse), Lepadella costatoides (Segers), Platyias quadricornis (Ehrenberg), Trichotria tetractis (Ehrenberg), Camptocercus australis Sars, Eucyclops sp., and Tropocyclops sp. were encountered in both streams. Nine species of zooplanktons appeared only in Yakruea Stream, whereas 4 species occurred in Phromlaeng Stream.